The Effect of the Role of Nurses in Managing Pain on the Pain Scale of Postoperative Cranioctomy Patients in the ICU of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City - Farida Tute; Fadli Syamsudin; Harismayanti (Universitas Muhammadiyah Palu, 2026)
Background: The pain felt by the patient after undergoing craniotomy surgery is physical stimulation resulting from the incisions and traction used during craniotomy to stimulate specific terminal and nociceptoral nerves. One of the usual pain managements is finger palm relaxation. Objective: To determine the effect of finger grasp relaxation on the reduction of pain scale in patients after craniotomy surgery. Method: Using a quantitative method with a pre-experiment, pretest, posttest, one group design. The population and sample of the study were 10 respondents determined by the total sampling technique. Data collection was done using observation sheets. The data was analyzed using a statistical test of the pairet t test. Results: The average value of the pain scale before administration of the finger grip relaxation technique was 7.6 or the severe pain scale and after the intervention was 5.8 or the moderate pain scale. Conclusion: That there was an effect of giving finger grip relaxation techniques in reducing pain in patients after craniectomy surgery with a p value of 0.000 (? < 0.05). It is recommended to the implementing nurse to consider using finger grip relaxation therapy interventions as one of the nursing interventions in reducing pain.